(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2017)
Vito Mancuso, one of Italy’s most famous intellectuals and author of bestselling books on religion—such as The Soul and Its Destiny (2007) and I and God. A Guide for the Perplexed (2011)—is a secular theologian and philosopher of religion who promotes an anti-traditional understanding of Christianity aimed at lay people influenced by contemporary secular ideas. This paper investigates Mancuso’s notion of freedom, particularly freedom of conscience and freedom of religion, in the general context of his religious philosophy which focuses on the concept of soul. In Mancuso, reality is essentially material, so everything which exists in the world and the universe is part of this material reality. The human being is no exception; thus, its natural constitution is thoroughly material. Everything pertaining to the human being, including the idea of soul, is material. However, the fact that ideas, such as the soul, can be conceived within the materiality of the human being is indicative of the latter’s capacity for spiritualization; consequently, spirituality is also part of and constitutive of materiality. Hence, Mancuso’sbelief that the soul is material, and so is everything traditionally accepted as spiritual, including ideas such as God and freedom. Since freedom can beconnected to matter and materiality through the concept of soul, Mancusoargues that the reality of freedom is innate in every human being; men and women, however, must become aware of it and then live it out in their daily lives by promoting as well as defending freedom of conscience and freedom of religion. Both types of freedom are compulsory not only for the good of human kind in general, for peace, and security, but also for every particular human being who can lead an authentic life only by practicing freedom of conscience and freedom of religion.